The changing life cycle pattern in female employment: a comparison of Germany and the UK - Bernd Fitzenberger; Gaby Wunderlich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
It is often noted that employment rates of females have been rising during the last decades. However, in contrast to men, women are often part-time employed and the allocation of working time over the life-cycle is linked to family formation. In addition, employment rates may differ across skill groups and countries due to differences in incentives to work and in labor market attachment. This paper analyzes empirically macroeconomic trends and life-cycle profiles in full-time and part-time employment of different skill groups of women in the UK and West Germany. The analysis is based on large crosssectional data sets for a time period of 20 years. We find that patterns of part-time and full-time employment are surprisingly different across skill groups and countries. In particular, the life-cycle patterns are such that full-time employment declines and part-time employment increases with age in both countries. Time trends do not change in a monotonous way across skill groups and they differ by country. There is almost no evidence for a positive time trend in part-time employment thus the strong increase in part-time rates in both countries can mainly be attributed to composition effects. Our findings are based on an empirical model taking the effects of time, age, and birth cohort membership simultaneously into account.
Keywords: J2; J71; J16; 330; Part-time and Full-time Employment; Females; Cohort Analysis; Frauenerwerbstätigkeit; Teilzeitarbeit; Erwerbsverlauf; Lebenszyklus; Schätzung; Deutschland; Großbritannien